PENGARUH PELATIHAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR DESA SUKAMANTRI KECAMATAN TAMBELANG KABUPATEN - Nurkhotimah, Siti (PT Kimshafi Alung Cipta, 2022)
Progress Human resources have increased and are already familiar in the era of globalization and increasingly sophisticated technology, global competition cannot be avoided by companies and organizations. Good and professional performance is one of the benchmarks of progress and success of the Company and organization to conduct increasingly fierce global competition. This study aims to test, study and obtain the results of the effect of training, motivation and work discipline on the performance of Sukamantri Village Office employees Tambelang District Bekasi District individually or separately. This research was conducted on employees at Sukamantri Village office. This research uses a quantitative approach, and the data used are primary data obtained by distributing questionnaires. The method used in this research is multiple linear regression method using IBM SPSS version 26. The results of this study indicate that: (1) there is a positive and significant effect on training with the performance of Sukamantri Village office staff. (2) there is a positive and significant effect on the motivation variable with the performance of Sukamantri Village office staff. (3) and there is a positive and significant influence on the performance of Sukamantri Village office employees.